The Effect of Enterprise Characteristics and Self Efficacy on Entrepreneurial Decisions - Rakhmawati Purba; Sri Winda Hardiyanti Damanik (Universitas Muhammadiyah Jakarta, 2021)
Entrepreneurs are people who have a mental attitude and spirit who are always active, creative, innovative, inventive, initiative and trying to increase income by providing added value to society in their business activities. Young people have started to instill an entrepreneurial spirit since attending school by incorporating entrepreneurial lessons and practices in school. It is intended that after completing education in school, every student has the viewpoint of creating jobs that can support their needs and does not always have the view of working as an employee, both civil servants and private employees. The problem we are facing is that the unemployment rate is getting higher every day and generally after completing their education most of the students become unemployed because there are very few jobs and lack of costs to continue their education to a higher level. This study aims to determine the effect of entrepreneurial characteristics and self-efficacy on entrepreneurial decisions among Madrasah Aliyah students. The independent variables of this study are entrepreneurial characteristics and self-efficacy, while the dependent variable is entrepreneurial decisions. This research is a quantitative descriptive study. The population in this study were students of class XII Madrasah Aliyah. The sampling technique used in this study was purposive sampling technique with a total sample of 36 students. The data collection technique used was a questionnaire. The data analysis technique used is multiple linear analysis. The data used are primary data. The results showed that there was a positive and significant influence on entrepreneurial characteristics and self-efficacy on entrepreneurial decisions.